1993
DOI: 10.1016/0741-5214(93)90145-c
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the calf venous pump mechanism: Determinants of postexercise pressure

Abstract: The mechanism of ambulatory venous pressure reduction is complex and multifactorial. The importance of venous wall characteristics as a determinant of postexercise pressure has not been previously appreciated. Changes in venous wall property after a thrombotic process, for example, could conceivably influence ambulatory venous pressure and recovery time in the absence of reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 13 publications
2
27
1
2
Order By: Relevance
“…The cross-section of the veins is consequently reduced and the blood flow is accelerated (Ashton 1975;Bassez et al 1999;Chauveau 1999;Ogata and Whiteside 1982;Williams et al 1999). In addition, ECS may act like a stiff fascia, improving the efficacy of the muscle (calf) pump (Alimi et al 1994;Bassez et al 1999;Raju et al 1993) during dynamic muscle contractions.…”
Section: Introductionmentioning
confidence: 98%
“…The cross-section of the veins is consequently reduced and the blood flow is accelerated (Ashton 1975;Bassez et al 1999;Chauveau 1999;Ogata and Whiteside 1982;Williams et al 1999). In addition, ECS may act like a stiff fascia, improving the efficacy of the muscle (calf) pump (Alimi et al 1994;Bassez et al 1999;Raju et al 1993) during dynamic muscle contractions.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it has been speculated that EC garments can reduce venous stasis at rest and facilitate the venous return to the heart during exercise by increasing the efficacy of the muscle pump (Alimi et al, 1994;Raju et al, 1993). If EC garments improve the peripheral circulation by enhancing muscle pump, muscle fatigue should be reduced by wearing EC garments during fatiguing exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure-volume relationship is exclusively calculated for each individual, and the decrease in volume during exercise is converted into a decrease in pressure. This relationship between volume and pressure is not linear [29,32,33] and may therefore explain the poor relationship between results with APG and measurements of ambulatory venous pressure that is sometimes reported [32]. Furthermore, APG measurements are carried out in the standing position, allowing the blood to ' fall ' down the leg into the venous segments.…”
Section: Discussionmentioning
confidence: 97%
“…Perhaps the SVPT measures the muscle contraction that induces a venous collapse, pushing the venous blood cranially. Raju et al [33] observed narrowing of the popliteal and tibial veins after calf muscle contraction, using venography. Therefore a good muscle contraction and vein collapse must be possible in order to induce a decrease in pressure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation